Reducing energy use in UK transport - Banister, D (2007)
Draft paper for the BIEE Seminar on the energy White paper: An Academic Critique, to be held at Imperial College, 25th September 2007. Transport is making a very limited contribution to carbon emissions reduction targets in the UK, and this paper argues the case for a substantial shift in thinking away from the concentration on technological alternatives to one that combines technological efficiency with behavioural change. It presents a critique of the UK approach to energy and transport, commenting on the approach and measures used, and their effectiveness. The focus here is on the 2007 Energy White Paper, the Climate Change Programme and the Environmental Audit Committee report on carbon emissions from transport. The necessary policy measures are available, but at present there is not sufficient political and public support for effective action. Technology on its own will not be enough.